Answer:
No single Correct answer. Both b and d will work
Explanation:
You want to get rid of y.
The first equation has a 3 in front of the y
Therefore you would have to multiply the second equation by 3 or - 3
If you use -3 you would add the two equations
If you use 3 you would subtract the two equations.
It is either b or d. Both will give you the same answer.
- Three
x + 3y = 10
-6x - 3y = - 15 Add
-5x = - 5 Divide by - 5
x = -5/-5
x = 1
+ Three
x + 3y = 10
6x + 3y = 15 Subtract
-5x = - 5
x = -5/-5
x = 1 Same thing.